Effects of the Various Mixing Ratios of Recycled Pulp on the Physical and Optical Properties of Handsheets and their Curl due to Laser Printing - Somwang Khantayanuwong; Phornwilai Nithisoonthornphong; Warakorn Thunyakhunakornsakool; Sawitree Pisuttipiched (Agriculture and Natural Resources, 2008)
The objectives of this study were to determine the physical and optical properties of handsheets and also to ascertain the behavioral phenomena of their curl due to laser printing. Handsheets were separately produced from beaten hardwood, softwood and recycled pulp and also from various mixing ratios of the beaten pulp. The recycled pulp was derived from white wood-free shavings (WWFSs) and washed-WWFSs pulp slurries. The results demonstrated that hardwood and softwood pulp mixed with washed-WWFSs recycled pulp could produce higher apparent density handsheets than those mixed with WWFSs recycled pulp, even though the increased amount of WWFSs and washed-WWFSs recycled pulp used for making handsheets decreased the apparent density and tensile strength of handsheets. Most of the various ratios of WWFSs recycled pulp mixed with hardwood and softwood pulp could give slightly higher brightness and opacity handsheets than most of those of washed-WWFSs recycled pulp mixed with the same hardwood and softwood pulp. With laser printing, handsheets printed on their bottom side were curlier than those printed on their top side. This is possibly because a greater amount of inorganic materials, which was demonstrated in terms of ash content, derived from fillers and coating pigments were retained in the top side of the handsheets. The increase in ash content of handsheets also decreased the amount of curl. In this study, it is especially noteworthy to demonstrate that without any inorganic materials retained in handsheets, both the handsheets printed on the top and the bottom side had the same amount of curl.